What happens when I look at you: the intimate space of prison theater (Urdimento - Revista de Estudos em Artes Cênicas, 2020)
Despite the burgeoning literature on theater and volunteers in prisons, there is little research that looks at the prison theater experience through the eyes of both the outside volunteers and the prisoner-participants.  This article seeks to weave together the voices of the co-authors in order to explore shared experiences of the prison theater classroom. These experiences – variously described as ‘magical’ and ‘transcendent’ – are dependent on the volunteer successfully navigating entry into the prison. The space of the prison theater classroom then becomes a relational refuge where both prisoners and volunteers can feel welcome and accepted, seen not as other but as essential.
Keywords: Teatro na prisão; Artes prisionais; Voluntários na prisão; Reabilitação; Artes em correções